Pemanfaatan Ubi Ungu Sebagai Makanan Kesehatan Dalam Upaya Peningkatan Derajat Kesehatan dan Kesejahteraan Masyarakat Petani di Desa Mekar Jaya Kecamatan Duhiadaa Kabupaten Pohowato - Madania, Madania; Hasan, Hamsidar; Thomas, Nur Ain (Dewan Pimpinan Daerah (DPD) Forum Dosen Indonesia JATIM, 2017)
The potency of purple sweet potatoes cultivation in Mekar Jaya Village, Duhiadaa Sub-district, PohowatoRegency is abundant but only sold in the form of tuber. Average selling price of the tuber is Rp. 7,000, - which is stillincluded in the very low price category and the demand is still small. To be able to increase the selling point, it isnecessary to inform the community in the village both knowledges and skills in terms of raw management of the tuber intoflour and subsequently it can be made into a healthy food with high nutritional value and also to increase the sellingvalue so as to improve the welfare of the community. This activity aims to improve the knowledges and skills of thecommunity in making healthy food from the tuber. This health foods such as ice cream with high nutritional value,brownies and low carbohydrate bread, and potato sticks with high antioxidant content is one of the alternative fooddestined for diabetics, cholesterol due to the nutritional content and fiber. The empowerment model in transferringknowledges and technology to the group of Pembinaan Kesejahteraan Keluarga (PKK) in the village is using directpractice method in the field, starting from the process of making products from the tuber to product marketing. Thisactivity involves the supervisors (Dosen Pembimbing Lapangan, DPL), students, extension workers as partners in KKNPPM (Kuliah Kerja Nyata - Pembelajaran Pemberdayaan Masyarakat) activities that is a very important institution related to the activities undertaken and involved in the development of agricultural commodities development.  The form of the implemented program are socialization by the students about the benefits of the tuber and direct practice about how tomake healthy products such as making bread, brownies, ice cream and potato sticks, packaging and marketing accordingto the needs. The method used is empowerment of PKK Mekar Jaya group with instructional techniques and directpractice by providing knowledges about how to produce a high quality products from the purple sweet potatoes which iscapable to compete in the market